1997
DOI: 10.1093/hmg/6.7.1147
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations in the human glutathione synthetase gene result in severe metabolic acidosis, 5-oxoprolinuria, hemolytic anemia and neurological dysfunction

Abstract: Severe glutathione synthetase (GS) deficiency is a rare genetic disorder with neonatal onset. The enzymatic block of the gamma-glutamyl cycle leads to a generalized glutathione deficiency. Clinically affected patients present with severe metabolic acidosis, 5-oxoprolinuria, increased rate of hemolysis and defective function of the central nervous system. The disorder is inherited in an autosomal recessive mode and, until recently, the molecular basis has remained unknown. We have sequenced 18 GS alleles associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…The most frequent hallmarks are 5-oxoprolinuria, metabolic acidosis and hemolytic anemia, and in severely affected patients, the central nervous system is affected. This deficiency is caused by mutations in the GSS gene and more than 30 mutations have been described which are transmitted in an autosomal recessive fashion (Al-Jishi et al 1999;Dahl et al 1997;Njalsson et al 2003;Shi et al 1996). Heterozygous carriers of GSS mutations are healthy and show an enzyme activity of 55% of the normal mean and normal levels of GSH .…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent hallmarks are 5-oxoprolinuria, metabolic acidosis and hemolytic anemia, and in severely affected patients, the central nervous system is affected. This deficiency is caused by mutations in the GSS gene and more than 30 mutations have been described which are transmitted in an autosomal recessive fashion (Al-Jishi et al 1999;Dahl et al 1997;Njalsson et al 2003;Shi et al 1996). Heterozygous carriers of GSS mutations are healthy and show an enzyme activity of 55% of the normal mean and normal levels of GSH .…”
Section: Introductionmentioning
confidence: 99%
“…Screening methods such as single strand conformational polymorphism (SSCP) with a sensitivity of approximately 70-90 % to detect mutations in the analyzed exons is likely to detect merely 50-70 % of the mutations in families with GS deficiency, considering the present report of seven of 30 families exhibiting intronic mutations. Given the large number of different mutations in the GSS gene (Shi et al, 1996;Dahl et al, 1997), screening for already reported mutations in new patients, by e.g. allele specific PCR, is of limited value.…”
Section: Discussionmentioning
confidence: 99%
“…In the second step, catalyzed by glutathione synthetase (GS), glycine is added to form the tripeptide. We and others have described inherited defects in both steps, and the diagnosis can be established based on a combination of biochemical, clinical, and genetic data (Shi et al, 1996;Dahl et al, 1997;Al-Jishi et al, 1999;Ristoff et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Complete loss of function of both GS alleles is probably lethal. Missense mutations will account for the phenotype in the majority of patients with severe GS deficiency (Dahl et al, 1997). A 141-bp deletion corresponding to the entire exon 4, whilst the corresponding genomic DNA showed a G491→A homozygous splice site mutation, and a C847→T (Arg283→ Cys) mutation in exon 9 are described in patients with GS deficiency and Fanconi nephropathy (Al-Jishi et al, 1999).…”
Section: Point Mutation In Glutathione Synthetasementioning
confidence: 99%